2017
DOI: 10.1101/153775
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A National Estimate of the Health and Cost Burden ofEscherichia coliBacteraemia in the Hospital Setting: The Importance of Antibiotic Resistance

Abstract: Background: Antibiotic resistance poses a threat to public health and a burden to healthcare systems. Escherichia coli causes more bacteraemia cases in England than any other bacterial species, these infections, in part due to their high incidence, also pose a significant antibiotic resistance burden. The main aim of this study was to estimate the impact of E. coli bacteraemia on patient inhospital mortality and length of stay. Secondarily, this study also aimed to estimate the effect of antibiotic resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Especially the impact on ICU discharge may have been underestimated, given the fact that a recent English study found that antibiotic resistance among E. coli increases length of stay, but did not seem to have a significant impact on inhospital mortality. 29 In our study, even after adjusting for the timing of acquiring bacteraemia and time-varying confounding using IPW for marginal structural models, ICU-acquired bacteraemia was associated with a substantial increased daily risk of ICU mortality and decreased daily ICU discharge risk. Gender was coded as a binary variable with male gender set to 1.…”
Section: Strengths and Limitationsmentioning
confidence: 55%
“…Especially the impact on ICU discharge may have been underestimated, given the fact that a recent English study found that antibiotic resistance among E. coli increases length of stay, but did not seem to have a significant impact on inhospital mortality. 29 In our study, even after adjusting for the timing of acquiring bacteraemia and time-varying confounding using IPW for marginal structural models, ICU-acquired bacteraemia was associated with a substantial increased daily risk of ICU mortality and decreased daily ICU discharge risk. Gender was coded as a binary variable with male gender set to 1.…”
Section: Strengths and Limitationsmentioning
confidence: 55%
“…For (iii), background patient utility was summed over remaining life expectancy, estimated using McCabe score (1¼background life expectancy, 2¼five years, 3¼one year). CABSI in-hospital mortality and excess LOS were estimated from NHS patients with E. coli bacteraemia using a previously linked HES/DCS dataset and methods described elsewhere [18]. Burden was considered from the perspective of NHS trusts with a one-year time horizon over FY2016/17, although future QALYs lost to chronic sequelae and mortality were considered over a lifetime horizon and discounted annually at 3.5% [25].…”
Section: Quantifying Disease Burdenmentioning
confidence: 99%
“…Antimicrobial resistance is a global health threat to clinical practice and public health [ 1 , 2 , 3 , 4 ]. It is estimated that the continued rise in multidrug resistance (MDR) will cause 10 million people to die worldwide by 2050 and cost 100 trillion USD [ 5 ].…”
Section: Introductionmentioning
confidence: 99%